TEKNIK PENYUNTINGAN GAMBAR DENGAN MENCIPTAKAN KESINAMBUNGAN GAMBAR DALAM FILM PENDEK “SRIHUNNING KANTHIL” - Mochammad Rizki Fauzzi; Dwi Nurrahmi K.; Arif Budiman (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTThe making of this work aims to describe the work of editors in films relating tothe post-production process, including Logging, Offline Editing, Online Editing, Mixing,Distribute. As for the background for the making of the short film "SRIHUNNINGKANTHIL", the local culture of Indonesia is still thick with the spiritual, mythical, andhumanistic aspects. To produce a work, especially film, editing technique becomes one ofthe important aspects that must be present. With image editing techniques, it will createa work that is sustainable with the story line for the creation of aesthetic value. Themethod used is observation and interview. At the observation stage the authors payattention to the screening screened by film communities and sharing with the filmmakerswho screened. The interview stage, the writer interviewed several figures, including akejawen expert who had some experience that he had experienced and also as a formerpalace man of the palace.In editing techniques include aspects of editing (graph continuity, rhythmic,spatial and temporal aspects), editing forms (cut, fade in / out, dissolve and wide), andediting continuity. The image editing process used in the short film "SRIHUNNINGKANTHIL" namely graphics, coloring, masking and subtittle. One of the image editingtechniques used is in scene 1, namely cut to, dissolve, and crosscutting. Dissolve is atransition effect, while moving to the next scene uses the cut technique. Film is one artthat is different from other arts. Because it stands from several elements of literary arts,theater arts, fine arts, sound, music, and architecture. Film editing is an important thingin film because film editing is a high and key art of the final productions of filmproduction. Image editing technique is one of the important editing processes to producean aesthetic work that can be enjoyed by connoisseurs of art.Keywords: Work, Film, Editing, Continuity